Effect paths of environmental factors and community attributes on aboveground net primary productivity of a temperate grassland. (7th May 2021) - Peng, Zhaoyu; Liu, Hongyan; Jiang, Lubing; Liu, Xu; Dai, Jingyu; Xu, Chongyang; Chen, Zhiting; Wu, Lu; Liu, Feng; Liang, Boyi
Abstract: Aboveground net primary productivity (ANPP) of grassland influenced by both environmental factors and structural plant community attributes indicates its growth situation and ability to provide ecosystem services. However, previous works have focused on the effects of either environmental factors or plant community attributes on ANPP, which makes it difficult to quantify the effect pathways of environmental factors and plant community attributes on ANPP. In our study, we took a temperate grassland in the agropastoral ecotone of northern China as the research area and quantified the effects of environmental factors and plant community attributes on grassland ANPP with a structural equation model, together with correlation and partial correlation analyses. We found that growing season precipitation is the most critical factor for grassland ANPP, and its direct effect (standardized direct positive effect, SDE = 0.401, p  < 0.05) on ANPP was the main path. Temperature affected ANPP directly (SDE = 0.230, p  < 0.05) and indirectly (standardized indirect positive effect SIE = 0.110, p  < 0.05) mainly through community attributes in the area, such as tiller number and cover. The increase in soil sand content reduced tiller number and further affected ANPP (SIE = 0.011, p  < 0.05). Human population influenced ANPP through species diversity (SIE = −0.059, p  < 0.05), and the increase in livestock number worked on ANPP by degrading the soil. Our results imply that improving grassland community attributes, such as maintaining species diversity and increasing vegetation coverage, will effectively mitigate the negative effects of climate change.